Sodium phosphorus transporter DvSPT2 inducible promoter, cloning method and use thereof - SONG RENTAO; ZHANG WENWEN; MENG XIANGZONG; GUAN ZHENWEI; LI GAOMIN; LU BIN; XU ZHENGKAI (2008)
The invention relates to a DvSPT2 gene induction-based promoter of a sodium-phosphorus transporter, a method for cloning the same and application of the promoter. Positive clones are sequenced by screening a salt algae genomic library to obtain a promoter area containing an upstream regulatory sequence of Number 2 gene (DvSPT2) of a co-transportation passage for salt algae and sodium-phosphorus. Analysis of the promoter area shows that the promoter area has a plurality of cis-acting elements which possibly join multiple adversity stress. By the detection of a controlled expression mode of DvSPT2 under the adversity condition, DvSPT2 is subject to the obvious induction under these adversities, which shows that promoter area and the regulatory sequence at the upstream of the DvSPT2 gene play an important role in adaptation of the salt algae adversity. As the promoter induced by an adversity signal, the promoter area and the upstream regulatory sequence of the DvSPT2 gene have important values in application of